Dog‐assisted interventions in care homes: A qualitative exploration of the nature, meaning and impact of interactions for older people. (23rd October 2020) - Jain, Briony; Hafford‐Letchfield, Trish; Ellmers, Toby; Chandra, Carl; Billings, Barbara; Teacher, Ruth; O'Farrell Pearce, Sioban; Clancy, Carmel
Abstract: Dog‐assisted interventions (DAI) have been shown to have a wide‐range of potential benefits for older adults living in care homes. Yet, there is a lack of published qualitative research which explores the experiences of care home residents, staff and dog‐owner volunteers involved in DAI to fully understand its meaning, impact and value. This study aimed to explore the impact of a DAI on the social and emotional wellbeing of older residents living in care homes. The research employed a qualitative study design comprising overt, naturalistic researcher observation of weekly DAI sessions with 54 older adult residents across four participating care homes in the South East region of England over 3 months in 2018. Data were also collected through focus groups with 12 care home staff and 7 dog‐owner volunteers. The data from the observations and focus groups was individually coded followed by thematic analysis across the three data sources. Findings demonstrated there were clear benefits for older people who engaged with DAI, as well as for dog‐owners and to some extent for care home staff members. Benefits included sensory, emotional stimulation and opportunities for social interaction, reminiscence on early life experiences and these were supported by the development of some new social relationships. While there were some environmental challenges to implementing DAI, the findings confirm its value for care home residents, with minimal drawbacks from an organizational standpoint. As a low cost intervention, adoption of DAI in care home settings appeared to strengthen relationships between residents and staff and enable wider relationships with an external community resource.